KONSENTRASI POLYCHLORINATED BIPHENYLS (PCBS) DAN POLYCHLORINATED DIBENZO-P-DIOXINS/POLYCHLORINATED DIBENZOFURANS (PCDDS/FS) DALAM AIR DARI DAERAH PERKOTAAN JABODETABEK - Shoiful, Ahmad; Nugroho, Rudi; Fujita, Hiroyuki; Honda, Katsuhisa (Center for Environmental Technology, 2014)
Determination of polychlorinated biphenyls (PCBs) and polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDDs/Fs) in water samples from Jabodetabek urban area was conducted. In the results, a unique pattern were found interestingly in Ciliwung river, Pluit, Jakarta, where decachlorinated biphenyl (PCB IUPAC #209), and dichlorinated biphenyl (PCB IUPAC #11) were detected at relatively high concentrations as 406.77 ng/L and 6.38 ng/L, respectively. This congener pattern is different with commercial PCB mixtures, such as arochlor, kanechlor, or chlophen. Octachlorinated dibenzo-p-furan (OCDF) was also detected at a significant concentration in this water as 3.10 ng/L. Decachlorinated biphenyl (PCB IUPAC #209) and OCDF were associated with industrial by-products. Meanwhile, dichlorinated biphenyl (PCB IUPAC #11) was associated with colour pigment which widely used in consumer goods, such as paint and printed ink. Thus, PCBs and PCDD/Fs contamination might have arisen from industrial by-products where various industries located near sampling point.Ã‚Â Keywords: polychlorinated biphenyls (PCBs), polychlorinated dibenzodioxins /polychlorinated dibenzo-p-furans (PCDDs/Fs), waters, Jabodetabek, industrial by-products.